Effect of modified atmosphere storage on the shelf life and quality of black pepper and turmeric - K N Shiva, T J Zachariah, E Jayashree, (Journal of Spices and Aromatic Crops, 2019)
Modified atmosphere packaging and storage of black pepper (var. Panniyur I) and turmeric (var. Prathiba) were studied for a period of 16 months under ambient storage conditions. Whole dry samples of black pepper and turmeric were packaged in three layered metalized polyester covers (12 μ polyester + 12 μ metalized polyester + 80 μ LDPE) under three modified storage atmospheres viz. 100% vacuum, 100% N2, 90% N2 + 10% CO2 and the control samples were stored in small size jute gunny bags. Results indicated that maximum retention of quality in terms of its essential oil and oleoresin contents of black pepper and turmeric was obtained when stored under nitrogen packaging (100% N2), followed by vacuum packaged (100% vacuum) and modified atmosphere storage of 90% N2 + 10% CO2. The essential oil content of stored black pepper reduced from 2.42% to 2.22% (dry weight basis, dwb) in all the three modified atmosphere storage with a loss of 8.26% while control recorded a loss of 16.53% during storage. The oleoresin content decreased from 7.79% to 7.44%, 7.38% and 7.32% in case of black pepper stored in 100% N2 packaged, 100% vacuum packaged and 90% N2 + 10% CO2 packaged storage atmospheres. The quality loss for turmeric in terms of essential oil, oleoresin and curcumin content at the end of storage, when packaged in 100% N2 atmosphere were 36.60%, 16.12% and 9.48%, respectively while the corresponding reduction in control samples were 40.49%, 20.27% and 19.39%.